2017
DOI: 10.1186/s13568-017-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics, fatty acid composition and metabolic activity changes of Crypthecodinium cohnii under different nitrogen source and concentration

Abstract: The effect of varying concentrations of the nitrogen source on the growth kinetics, lipid accumulation, lipid and DHA productivity, and fatty acid composition of C. cohnii was elucidated. Growth of C. cohnii was in three distinct growth stages: cell growth, lipid accumulation and a final lipid turnover stage. Most of lipids were accumulated in lipid accumulation stage (48–120 h) though, slow growth rate was observed during this stage. NaNO3 supported significantly higher lipid content (26.9% of DCW), DHA conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 48 publications
4
20
0
1
Order By: Relevance
“…In general, any oleaginous microorganism channels excess carbon toward the accumulation of triacylglycerol under conditions in which a key nutrient (such as nitrogen) is exhausted. However, in a different study with some marine and freshwater species such as Crypthecodinium cohnii and C. sorokiniana , it was suggested that the lipid accumulation may not be due to exhaustion of a nutrient but also due to the excess carbon in the culture medium [ 39 , 40 ]. The accumulation of lipid in oleaginous microorganisms is not only dependent on the lipid-synthesizing enzymes associated with nitrogen starvation but also on the cessation of other enzymes involved in cell growth and proliferation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, any oleaginous microorganism channels excess carbon toward the accumulation of triacylglycerol under conditions in which a key nutrient (such as nitrogen) is exhausted. However, in a different study with some marine and freshwater species such as Crypthecodinium cohnii and C. sorokiniana , it was suggested that the lipid accumulation may not be due to exhaustion of a nutrient but also due to the excess carbon in the culture medium [ 39 , 40 ]. The accumulation of lipid in oleaginous microorganisms is not only dependent on the lipid-synthesizing enzymes associated with nitrogen starvation but also on the cessation of other enzymes involved in cell growth and proliferation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Placing emphasis on differences among the microorganisms and aiming for the most suitable metabolic spot leads to improvements in lipid yields and modification of lipid profiles. The wild-type strains can be modified to improve the lipid accumulation by using the recent metabolic engineering tools [77,161,[228][229][230][231][232][233][234][235][236][237]. The methods of metabolic engineering technology interfere at parts or whole of the proteome, lipidome, transcriptome, genome, and metabolome of microorganisms.…”
Section: Application Of Metabolic Engineering Technologies To Improvementioning
confidence: 99%
“…Interestingly, these exogenous oxidant stresses induce significantly of the lipid accumulation, especially triacylglycerol (TAG) which is suitable used as biodiesel feedstock (15). On the other hand, Safdar et al (16) revealed that during the extended nitrogen starvation, enzymes of tricarboxylic acid (TCA) cycle are downregulated whereas enzymes of lipid biosynthesis are upregulated. This in turn redirect substrate of citrate from TCA cycle to lipid biosynthesis ( Figure 1).…”
Section: Macronutrients Affecting Microalgal Growth and Biochemical Cmentioning
confidence: 99%